Building a Co-ordinated Musculoskeletal System: The Plasticity of the Developing Skeleton in Response to Muscle Contractions - Murphy, Paula; Rolfe, Rebecca (Springer Nature, 2023)
The skeletal musculature and the cartilage, bone and other connective tissues of the skeleton are intimately co-ordinated. The shape, size and structure of each bone in the body is sculpted through dynamic physical stimuli generated by muscle contraction, from early development, with onset of the first embryo movements, and through repair and remodelling in later life. The importance of muscle movement during development is shown by congenital abnormalities where infants that experience reduced movement in the uterus present a sequence of skeletal issues including temporary brittle bones and joint dysplasia. A variety of animal models, utilising different immobilisation scenarios, have demonstrated the precise timing and events that are dependent on mechanical stimulation from movement. This chapter lays out the evidence for skeletal system dependence on muscle movement, gleaned largely from mouse and chick immobilised embryos, showing the many aspects of skeletal development affected. Effects are seen in joint development, ossification, the size and shape of skeletal rudiments and tendons, including compromised mechanical function. The enormous plasticity of the skeletal system in response to muscle contraction is a key factor in building a responsive, functional system. Insights from this work have implications for our understanding of morphological evolution, particularly the challenging concept of emergence of new structures. It is also providing insight for the potential of physical therapy for infants suffering the effects of reduced uterine movement and is enhancing our understanding of the cellular and molecular mechanisms involved in skeletal tissue differentiation, with potential for informing regenerative therapies.
Roles of Skeletal Muscle in Organ Development
PUBLISHED
Keywords: Skeletal development, mechanoregulation, muscle immobilisation, tendon, joint; Genes & Society; Developmental Biology; MUSCULOSKELETAL SYSTEM; Zoology